2019
DOI: 10.1038/s41598-018-35983-3
|View full text |Cite
|
Sign up to set email alerts
|

SOX2 participates in spermatogenesis of Zhikong scallop Chlamys farreri

Abstract: As an important transcription factor, SOX2 involves in embryogenesis, maintenance of stem cells and proliferation of primordial germ cell (PGC). However, little was known about its function in mature gonads. Herein, we investigated the SOX2 gene profiles in testis of scallop, Chlamys farreri. The level of C. farreri SOX2 (Cf-SOX2) mRNA increased gradually along with gonadal development and reached the peak at mature stage, and was located in all germ cells, including spermatogonia, spermatocytes, spermatids an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…Our evidence hints that the sex QTL may be the same in this species and provides the foundation for mapping the master sex-determining gene in the future. We found the gene SOX2 located in the sex QTL interval, which has been reported to be necessary for the normal development and function of the hypothalamo-pituitary and reproductive axes in humans and in mice (Kelberman et al, 2006), and also supposed to be essential in spermatogenesis and testis development in Chlamys farreri (Liang et al, 2019). However, the actual sex-determining gene is far from being discovered, with the fact that the sex determining varies in gene and form, such as piRNA in silkworms and alternative splicing in Drosophila melanogaster (Biedler and Tu, 2016) and SOX2 is located far from the supposed master sex-determining gene.…”
Section: Discussionmentioning
confidence: 97%
“…Our evidence hints that the sex QTL may be the same in this species and provides the foundation for mapping the master sex-determining gene in the future. We found the gene SOX2 located in the sex QTL interval, which has been reported to be necessary for the normal development and function of the hypothalamo-pituitary and reproductive axes in humans and in mice (Kelberman et al, 2006), and also supposed to be essential in spermatogenesis and testis development in Chlamys farreri (Liang et al, 2019). However, the actual sex-determining gene is far from being discovered, with the fact that the sex determining varies in gene and form, such as piRNA in silkworms and alternative splicing in Drosophila melanogaster (Biedler and Tu, 2016) and SOX2 is located far from the supposed master sex-determining gene.…”
Section: Discussionmentioning
confidence: 97%
“… 35 Once knockdown of Sox2 expression occurs, spermatogenic failure is observed in the male gonadal tissue characterized by an array of reduced germ cells and a number of apoptosed spermatocytes, suggesting that Sox2 plays an important role in the development of male gonadal tissue and spermatogenesis. 35 In Labeo rohita , the presence of strong expression of Sox2 in spermatogonial stem cells is most likely to be linked with germ cell development and stem cells maintenance of fish, as evidenced earlier in case of human embryonic stem cells. 36 In fish, Sox2 is considered as a biomarker for undifferentiated spermatogonial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, further studies should investigate the expression pattern of the Sox9 gene in earlier developmental stages. In this study, we found that the golden mussel transcriptome has transcripts similar to other Sox family genes, such as Sox17, SoxB2, Sox4, Sox5, and Sox2, which was already suggested to play key roles in spermatogenesis and testis development in adults specimens of the scallop Chamys farreri (66).…”
Section: Identification Of Potential Sex Differentiation Genes In mentioning
confidence: 58%